Curriculum Management in Improving the Quality of Education in Indonesia - Neliwati Neliwati; Rafly Prahmana Hidayat; Rizki Ade Yusuf (Edumaspul: Jurnal Pendidikan, 2024)
The purpose of this study is to assess curriculum management in an effort to improve education standards. To find out the function of curriculum management in improving quality, literature research is the methodology used. Human resource development through education. Initiatives to improve education standards must be supported by all parties, including managers of central, regional and local education institutions. Decentralization of education with a quality improvement curriculum that is specific to each region is what we should see in the era of regional autonomy. Education programs that have been established by the central government should be expanded or implemented using this curriculum. With this curriculum in place, lower-level schools and local governments can create initiatives to improve the quality of education. In order to improve education, local governments will face competition with each other.